Westward into Kentucky : The Narrative of Daniel Trabue - Trabue, Daniel, 1760-1840 (Book collections on Project MUSE., 2004)
In his youth Daniel Trabue (1760--1840) served as a Virginia soldier in the Revolutionary War. After three years of service on the Kentucky frontier, he returned home to participate as a sutler in the Yorktown campaign. Following the war he settled in the Piedmont, but by 1785 his yearning to return westward led him to take his family to Kentucky, where they settled for a few years in the upper Green River country. He recorded his narrative in 1827, in the town of Columbia, of which he was a founder. A keen observer of people and events, Trabue captures experiences of everyday life in both the.